Oltre il confine stabilito. Teoria e funzionamento dei “controlimiti” (Stato, Chiese e pluralismo confessionale, 2017)
SOMMARIO: 1. I controlimiti: osservazioni introduttive - 2. Controlimiti nella giurisprudenza della Corte costituzionale italiana: le norme europee - 3. (segue): controlimiti e norme concordatarie - 4. (segue): controlimiti e norme internazionali pattizie ex art. 11 Cost. - 5. Norme internazionali generalmente riconosciute: adattamento automatico al diritto internazionale e funzionamento dei controlimiti - 6. La giurisprudenza dei controlimiti internazionali - 7. La sentenza n. 238 del 2014 e la tutela dei diritti inalienabili della persona contro i crimini di guerra: motivi di una decisione - 8. Profili processuali delle pronunce del 2014-2015. Chi applica i controlimiti e su che cosa si svolge il giudizio? - 9. L’inesistenza delle norme contrarie a principii supremi e l’applicazione dei controlimiti - 10. Conclusioni: dalle pronunce del 2014-2015 a un ripensamento del funzionamento dei controlimiti in generale?ABSTRACT: The essay analyses the doctrine of “controlimiti”, theorized by the Italian Constitutional Court in order to garantee the infringed fundamental rights and principles. Firstly, they will be recalled the main decisions concerning the limits to the European, concordatory and international law. Secondly, they will be analysed the decisions adopted in 2014 and in 2015, relating to the customary international law. According to these last decisions, the Constitutional Court seems to stress a different modus operandi of the controlimiti doctrine. In fact, when the Italian Court declares the contrast between corcordotary or European law and constitutional fundamental principles, the external rules are “eliminated” by declaring the invalidity of the internal rules, which reproduces the European or concordatory law. Instead, in 2014-2015 the Constitutional Court decides to declare the inexistence of the rules, which infringe the fundamental principles. Therefore, the essay will propose another possible way to reconstruct the controlimiti modus operandi, which is to consider that the Constitutional Court disapplies the rules, as they conflict with fundamental principles.